Different Control Schemes for Sensor Less Vector Control of Induction Motor - Srinivas Gangishetti; Tarakalyani Sandipamu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper deals with the design of different control schemes for sensorless vector control of induction motor.Induction motor is most widely used A.C. Motor but  the major draw back is flux and torque cannot be controlled individually.This can be obtained by implementing  sensorless vector control methods.The control strategy of induction motor  is by different controllers like conventional control methods and artificial intelligence control methods.The conventional control methods are sensitive to parameter changes and will not be accurate. This paper proposes to design a controller to over come the above draw backs by using intelligent control techniques like fuzzy logic, artificial neutral networks (ANN) and genetic algorithm (GA).The above conventional control methods are compared with intelligent control techniques. The simulation studies are carried out using Matlab/Simulink and the wave forms for speed, torque and voltage components for various controlles are plotted. Numerical analysis for speed and torque components considering parameters like peakover shoot and peak time are presented.